Strategi Implementasi Sistem Ticketing Menggunakan DewaCloud - Darwin Ng; Riche Suwandy (Jurnal Pengabdian Masyarakat (abdira), 2022)
Flexible server infrastructure training at a competitive cost was introduced through a webinar at DewaTalks. This training explains how to implement a ticketing system using DewaCloud which has a cloud architecture through the Platform-as-a-Service (PaaS) business model and is compared to building a ticketing system from scratch. Participants who take part in the training are developers who do not or do not have knowledge of server infrastructure. The ticketing system that has been implemented can be agilely adjusted or changed without any doubt because of the time spent on implementation. The result of this training is that 10% of the participants started using DewaCloud as a PaaS solution for their ticketing system needs.